Sklanjatev in naglas samostalnikov a-jevske sklanjatve v govoru vasi Jevšček pri Livku nadiškega narečja slovenščine - Šekli, Matej (Annales. Series historia et sociologia, 2007)
In the article the declension and the accentuation of a-stem nouns in the local dialect of Jevšček near Livek (Municipality of Kobarid, Slovenia) of the Nadiško (Nadiža/Natisone) (Nad.) dialect of Slovenian are discussed, from the diachronic and the synchronic point of view. The descriptive-linguistic perspective presents the inventory of endings and their distribution as well as the accent classes and their paradigmas. The historical-linguistic point of view determines the origin of endings and accent classes and also ascribes to the described morphological and accentual systems its position in the context of Slovenian and other Slavic languages.
Keywords: dialect; dialectology; dialektologija; nadiško narečje; naglasoslovje; narečja; skladnja; Slovene; slovenščina; syntax; zgodovinsko jezikoslovje